Characterization of monoclonal antibodies against a human chondrocyte surface antigen - Theerawut Chanmee (2018)
Chondrocytes express a number of cell-surface molecules that mediate cell-cell or cell-matrix interactions. Identification and full characterization of new chondrocyte surface molecules will lead to a better understanding of the function of the chondrocyte. Researchers used primary human chondrocytes as an immunogen, and various monoclonal antibodies (MAbs) were generated using standard hybridoma technology. A monoclonal antibody named 5D2 was selected for further characterization. The antigen recognized by 5D2 MAb is expressed by primary human chondrocytes, primary synovial fibroblasts, synovial fibroblast cell lines (SW982), primary skin fibroblasts, and osteoblasts, but not expressed in blood cells. Biochemical analysis revealed that the 5D2 antigen is a protein with a molecular weight of approximately 25-35 kDa. Protein identification by mass spectrometry and molecular cloning revealed that 5D2 antigen is identical to the Thy-1 molecule. Furthermore we confirmed this specificity of the antibody by the isolated and cloned Thy-1 gene to the COS-7 and probed it with the 5D2 antibody using Western blot analysis. We examined the role of the Thy-1 molecule in arthritis models and tissue; one was papain-induced rat arthritis, the other was immunohistological staining of osteoarthritic (OA) human articular cartilage. OA cartilage showed a higher expression of Thy-1 as compared with normal tissue in all experimental approaches. The in vitro studies showed that the inflammatory cytokine interleukin-1β up-regulated Thy-1 molecule expression in the cartilage tissue. It can be concluded that the Thy-1 might be a potential biomarker for cartilage pathogenesis, degradation, and metabolic turnover. © Copyright 2013, Mary Ann Liebert, Inc. 2013.